Differentiating the Whole Urine and Urine Supernatant Protein Profiles of Preterm Infants via Urine Proteomics - Lulu Zhang; Xueyan Wang; Dan Wu; Jun Zheng; Fangrui Ding (Kidney & Blood Pressure Research)
Introduction: Urine proteomics plays an important role in the screening of biomarkers for infant diseases. However, there is no unified standard for the selection of urine samples for urine proteomics. It is also unclear whether there are differences in proteomics between whole urine and urine supernatant. Therefore, the urine of preterm infants was used as the research sample to explore the differences in protein profiles between the whole urine and urine supernatant of preterm infants by proteomics. Methods: Urine samples were collected from five preterm infants with a gestational age of <28 weeks at their corrected gestational age of 37 weeks. Each preterm urine was divided into whole urine and supernatant. Urine protein was extracted and analyzed by liquid chromatography-tandem mass spectrometry. Results: The two groups of urine samples did not show significant clustering in the principal component analysis. A total of 2,607 proteins were detected in the two groups of urine samples, of which 82 proteins were unique to whole urine samples and 56 proteins were unique to urine supernatant samples. The molecular functions, the main biological processes, and subcellular localization of the differential proteins were analyzed. In other neonatal-related diseases, there was no significant difference in protein enrichment between whole urine and urine supernatant. Conclusions: This study analyzed the differences between whole urine and urine supernatant in urine proteomics of preterm infants. In neonatal-related diseases, there is no significant difference in urinary protein biomarkers between whole urine and urine supernatant.